2022
DOI: 10.21037/jgo-22-721
|View full text |Cite
|
Sign up to set email alerts
|

A novel senescence-associated LncRNA signature predicts the prognosis and tumor microenvironment of patients with colorectal cancer: a bioinformatics analysis

Abstract: Background: Accumulating evidence suggests that cellular senescence promotes tumor formation and that long non-coding RNAs (lncRNAs) expression predicts tumor prognosis. However, senescence-related variables, particularly lncRNAs, are still largely unknown. Therefore, the present study developed a novel senescence-associated lncRNA signature to predict colorectal cancer (CRC) prognosis.Methods: A co-expression network of senescence-associated mRNAs and lncRNAs was built using RNAsequence data from The Cancer G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It was also revealed that SNHG16 may serve a contributory role in the proliferation, migration and EMT of CRC cells through the miR-124-3p/MCP-1 axis ( 176 ). Some bioinformatics analyses also reached a similar conclusion, in that SNHG16 may have an important role in CRC ( 175 , 180 ). In particular, SNHG16 has been reported to be closely associated with autophagy in CRC ( 175 , 181 ).…”
Section: Snhg16 and Human Digestive System Cancermentioning
confidence: 58%
“…It was also revealed that SNHG16 may serve a contributory role in the proliferation, migration and EMT of CRC cells through the miR-124-3p/MCP-1 axis ( 176 ). Some bioinformatics analyses also reached a similar conclusion, in that SNHG16 may have an important role in CRC ( 175 , 180 ). In particular, SNHG16 has been reported to be closely associated with autophagy in CRC ( 175 , 181 ).…”
Section: Snhg16 and Human Digestive System Cancermentioning
confidence: 58%
“…This shows that senescent cells in TME are helpful and as valuable as other biomarkers in predicting prognosis and estimating the efficacy of immunotherapy of LUAD. Interestingly, other studies have also focused on the contribution of cellular senescence-associated LncRNAs to tumor prognosis in tumors including liver ( Huang et al, 2022a ), colorectal ( Huang et al, 2022b ), and gastric ( Wang et al, 2022 ) cancers. These studies have similar AUC values to the time-dependent ROC curves of our model and importantly illustrate the contribution of senescent cells to the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, lncRNAs are versatile molecules involved in various tumorigenic processes and offer the possibility of being used as biomarkers [ 9 , 10 ]. In patients with colorectal cancer (CRC), stomach adenocarcinoma, or Lung adenocarcinoma (LUAD), senescence-related lncRNA models have been developed and have certain predictive values [ 11 , 12 , 13 ]. However, the signature of senescence-related lncRNAs has not yet been established and applied to the prognosis prediction and clinical treatment of SKCM patients.…”
Section: Introductionmentioning
confidence: 99%